Real Exchange Rate Appreciation After the Financial Crisis of 2008-2009: Misalignment or Fundamental Correction? - Caputo-Galarce, R (WILEY, 2018)
In the aftermath of the 2008-2009 financial crisis, several emerging economies experienced substantial real exchange rate appreciations. From the point of view of policy makers, understanding the sources of these appreciations is crucial for designing efficient policy responses. The objective of this paper is twofold. First, we determine the extent to which appreciation episodes were determined by changes in fundamentals or if they constitute exchange rate misalignments. Second, we assess the impact that non-fundamental variables have on the real exchange rate dynamics. Based on a reduced form model, we conclude that appreciation episodes, in the aftermath of the 2009 financial crisis, can be explained by two elements: (i) an improvement in fundamentals and (ii) a correction of past misalignments. Hence, the real appreciation observed since 2010 was driven, mostly, by fundamental elements. In terms of policy implications, our results suggest that appreciations in that period should have been tolerated by policy makers.